2016
DOI: 10.1083/jcb.201603109
|View full text |Cite
|
Sign up to set email alerts
|

GEF-H1 is necessary for neutrophil shear stress–induced migration during inflammation

Abstract: In their work, Fine et al. demonstrate that GEF-H1 is required for the spreading and crawling of neutrophils in response to intravascular blood flow. They uncover a novel mechanism that couples shear stress with Rho-dependent migratory behavior of neutrophils during inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
34
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 53 publications
(75 reference statements)
2
34
0
1
Order By: Relevance
“…Although neutrophils are professional antimicrobial cells that are supposed to protect the organism against bacteria, their massive recruitment into tissues during sepsis harms the host. In line with this, Fine et al (2016) found that inhibiting septic leukocyte infiltration by neutrophil-specific GEF-H1 deletion increased mouse survival.…”
supporting
confidence: 54%
See 1 more Smart Citation
“…Although neutrophils are professional antimicrobial cells that are supposed to protect the organism against bacteria, their massive recruitment into tissues during sepsis harms the host. In line with this, Fine et al (2016) found that inhibiting septic leukocyte infiltration by neutrophil-specific GEF-H1 deletion increased mouse survival.…”
supporting
confidence: 54%
“… Fine et al (2016) noticed decreased neutrophil infiltration into the peritoneum of GEF-H1 −/− mice after inducing sterile peritonitis by thioglycolate injection. A similar neutrophil recruitment defect was seen after inducing sepsis by puncture of the mouse gut.…”
mentioning
confidence: 88%
“…Wild-type and Vav1-deficient neutrophils show the same migratory behavior under static conditions, highlighting that Vav1 is critical for shear-induced perpendicular crawling. Recently, Fine et al [57] further unraveled the underlying mechanism of shear stress-induced migration, specifically the role of the RhoA-specific GEF-H1 during neutrophil recruitment (Fig. 1A).…”
Section: Molecular Mechanismsmentioning
confidence: 98%
“…In slow migrating cells such as mesenchymal cells, MTs predominately radiate toward the leading edge, and the nucleus toward the cell rear . In these cells, MTs contribute directly to the protrusive forces, whereas in leukocytes, MTs indirectly affect actomyosin directed motility by controlling Rho GTPase activities …”
Section: Introductionmentioning
confidence: 99%